Transcriptome-wide m6A landscape across diverse porcine tissues revealed by nanopore direct RNA sequencing - Liao, Yaya; Ding, Zifeng; Chen, Xiaoyun; Yin, Chao; Yang, Bin; Yang, Qiang; Xing, Yuyun (Frontiers in Genetics, 2025)
N6-methyladenosine (m6A) is the most prevalent internal RNA modification in eukaryotic messenger RNA (mRNA). Pigs are valuable not only as a source of meat protein but also as ideal animal models for studying human diseases. To date, m6A has not been systematically mapped in a body-wide survey of porcine tissues. In this study, we used direct RNA sequencing data of 39 sow samples (from 23 tissues) and 7 fetal samples (from 7 tissues) to identify m6A modifications and alternative splicing (AS) events. In total, we identified 60,823 transcripts, including 27,823 novel isoforms. The mean poly(A) tail length varied markedly among tissues, ranging from 48 to 101 nt. A total of 343,951 m6A sites were identified, with sow and fetal samples averaging 80,336 and 92,476 sites, respectively. The number of m6A sites varied across different samples, ranging from 27,830 to 118,042. The brain samples displayed the most pronounced region-specific m6A pattern; different anatomical locations within the same tissue exhibited high m6A heterogeneity. Overall, m6A methylation levels were positively correlated with transcript expression levels; integrative analyses further supported an association between m6A modification and AS. Our findings provide novel insights that enhance our understanding of the regulatory complexity of the transcriptome and epitranscriptome in pigs.